Ras Activity Tunes the Period and Modulates the Entrainment of the Suprachiasmatic Clock - Serchov, Tsvetan; Heumann, Rolf (Frontiers in Neurology, 2017)
The small GTPase Ras is a universal eukaryotic intracellular cytoplasmic membrane-anchored protein, which regulates distinct downstream signal transduction pathways that play an important role in the proper functioning of neurons. Ras activity is a central regulator of structural and functional synaptic plasticity in the adult nervous system, where it channels neuronal responses to a variety of extracellular cues allowing the organism to adapt to complex environmental stimuli. The suprachiasmatic nucleus is the principle pacemaker of the circadian clock, and the circadian and photic regulation of Ras activity in the SCN is an important modulator of the clockwork. In order to study the possible role of neuronal Ras signaling, we have generated transgenic mouse model, which express constitutively active V12-H-Ras selectively in neurons via a synapsin I promoter (synRas mice). Ras activation enhances ERK1,2/CREB signaling and GSK3β activity in the SCN, modulating the photic resetting of the clock and fine tuning the circadian period length. The main focus of the present review is to offer an overview of the function of Ras signaling in the circadian rhythm and its potential role in learning and memory consolidation.